Dinamika Sosiolinguistik Masyarakat Dwibahasawan: Analisis Penggunaan Alih Kode dan Campur Kode dalam Interaksi Digital - Nur Syakila; Tessalonika Simangunsong; Lolo Mesliana Cibro; Ayu Nadira Wulandari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to describe and analyze the sociolinguistic phenomena of code-switching, code-mixing, interference, and integration in digital interactions among bilingual communities. The method used is descriptive qualitative, using listening and note-taking techniques for WhatsApp speech. The results show that code-switching occurs in whole sentences (Indonesian-English and Indonesian-Javanese), code-mixing occurs through the insertion of foreign terms such as "interview" and "gais" into Indonesian, integration is seen in religious terms that have become integrated into the language's rules, and morphological interference occurs in foreign verbs without appropriate affixes. This phenomenon is influenced by the social environment, limited word equivalents, and the need for social identity. The implications of this dynamic include increased communication flexibility, but potentially decreased the accuracy of standard language use in formal situations. Keywords: Sociolinguistics, Code-Switching, Code-Mixing, Bilingual Communities, Interaction.